Effects of interleukin-1 receptor antagonist in aged rats on spatial learning in the Morris water maze - Scruggs, Brandi, author (Colorado State University. Libraries, 2003)
Aging is a prevalent problem that has stimulated a great deal of research recently. Various changes in the physiological and psychological functioning of the aged individual have led to growing research interest in improving the quality of life for the elderly. The current study focused on age-related deficits in cognition, particularly learning and memory. One factor linked to age-related changes in learning and memory is interleukin-1β (IL-1β), which has been found in increased concentrations in aged animals, and has been shown to inhibit long-term potentiation and learning. The current study attempted to improve learning and memory in aged animals in the Morris water maze by injecting the interleukin-1 receptor antagonist (IL-1ra) intracerebroventricularly to block the effects of IL-1β. Concentrations of IL-1β in the brains of old versus young animals were also measured. It was expected that old animals would have the highest levels of IL-1β compared to young animals. It was also expected that IL-1β concentration would be negatively correlated with performance in the Morris water maze. Results showed that injections of IL-1ra did not effectively improve the learning of aged animals in the water maze. Results also showed that, contrary to previous research, young animals had the highest levels of IL-1β in their brains, while aged animals had the lowest concentrations. IL-1β concentrations were not correlated with performance in the water maze. Various interpretations of these results are discussed, as well as recommendations for future research.
Keywords: psychobiology